(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2024)
This study aimed to identify the effectiveness of electronic banking marketing methods used by Libyan banks in promoting and improving their banking services. In order to achieve this purpose, we relied on the descriptive method of scientific research to conduct this study. To collect the primary data of this study, A questionnaire form was designed and distributed to a sample of Libyan banks operating in the city of Sirte. The results of this study indicated that there was a statistically significant effect on the effectiveness of banking marketing methods in improving the quality of banking services. Therefore, the study recommended that it is advisable to Libyan banks to pay attention to diversifying banking marketing methods, especially electronic ones, in providing banking services, and spreading the culture of their use among bank customers.